Emotion in action : Thucydides and the tragic chorus - Visvardi, Eirene. (Mnemosyne, Supplements, 2015)
Emotion in Action: Thucydides and the Tragic Chorus offers a new approach to the tragic chorus by examining how certain choruses 'act' on their shared feelings. Eirene Visvardi redefines choral action, analyzes choruses that enact fear and pity, and juxtaposes them to the Athenian dêmos in Thucydides' History . Considered together, these texts undermine the sharp divide between emotion and reason and address a preoccupation that emerges as central in Athenian life: how to channel the motivational power of collective emotion into judicious action and render it conducive to cohesion and collective prosperity. Through their performance of emotion, tragic choruses raise the question of which collective voices deserve a hearing in the institutions of the polis and suggest diverse ways to envision passionate judgment and action.